The Association of Preoperative Malnutrition with Delayed Wound Healing and Related Postoperative Complications: A Systematic Review - Pretika Prameswari; Raka Jati Prasetya; Mutia Juliana (The Indonesian Journal of General Medicine, 2025)
Introduction: Preoperative malnutrition is a prevalent and modifiable risk factor in surgical patients, yet its full impact on postoperative recovery remains a critical area of clinical investigation. The objective of this systematic review is to comprehensively synthesize the existing evidence linking preoperative malnutrition to delayed wound healing and a broad spectrum of other adverse postoperative outcomes. Methods: A systematic search of the PubMed, EMBASE, and Cochrane Library databases was conducted to identify relevant observational studies and meta-analyses. Studies were selected if they investigated the association between a defined measure of preoperative malnutrition and postoperative outcomes in adult surgical patients. The methodological quality and risk of bias of included studies were rigorously assessed using the Cochrane "Risk Of Bias In Non-randomized Studies - of Interventions" (ROBINS-I) tool. Data were extracted for a minimum of 15 distinct outcomes, with a primary focus on wound healing complications. Results: Twenty-five studies, encompassing a wide range of surgical specialties and patient populations, met the inclusion criteria. The analysis revealed a consistent and statistically significant association between various markers of malnutrition—including hypoalbuminemia, low Prognostic Nutritional Index (PNI), and high Nutritional Risk Screening 2002 (NRS-2002) scores—and adverse postoperative events. Malnourished patients demonstrated significantly increased rates of surgical site infections (Odds Ratio range: 1.97 to 4.12), wound dehiscence (OR up to 3.24), and anastomotic leakage. Furthermore, malnutrition was strongly correlated with prolonged length of hospital stay (mean difference up to 5.58 days), increased 30-day mortality (OR up to 3.61), higher readmission rates, and a greater incidence of systemic complications such as pulmonary, cardiac, and renal events. Discussion: The synthesized evidence underscores the systemic impact of malnutrition on the physiological response to surgical stress and subsequent recovery. The findings suggest that nutritional deficiencies impair fundamental biological processes, including immune function and tissue synthesis, which are critical for uncomplicated wound healing. The clinical implications are significant, highlighting the necessity of integrating nutritional screening into routine preoperative assessment to identify at-risk patients who may benefit from targeted nutritional optimization. Conclusion: Preoperative malnutrition is a robust and independent predictor of delayed wound healing and a wide array of associated postoperative complications. The integration of routine nutritional assessment and appropriate intervention into standard preoperative care pathways is strongly recommended to improve surgical outcomes, reduce healthcare utilization, and enhance patient safety.